Biosorpsi Cu(II) oleh Pseudomonas putida - Lintang Elsa Valerina; Saffira Zhazhabila Maulida; Adriana Anteng Anggorowati; Shella Permatasari Santoso (Widya Teknik, 2020)
The one negative impact of industrial activities is the environmental pollution especially if contain heavy metals where the concentrations is exceed the Threshold Value (TLV). In this study, the biosorption of Cu (II) by Pseudomonas putida for reduce heavy metal in waste water. The biosorption with Pseudomonas putida was carried out in some initial variations of Cu (II), time adsorption, and pH. The concentration of Cu(II) after bisorption was measured using the UV-Vis spectrophotometry method. Based on the results of the study it was found that the greater initial concentration of Cu (II) from 8.000 ppm to 12.000 ppm the percentage decrease Cu (II) concentration is getting smaller. Whereas at the same initial concentration of Cu(II) 8.000 ppm the largest percentage reduction in Cu (II) concentration occurred at pH = 6 compared to pH = 4 and 5. This matter because metallothionein in the cell wall of Pseudomonas putida will be lysed under relatively acidic conditions at pH = 4 and pH = 5, if methallotionein lysis then the absorbed Cu (II) is smaller. In determining the biosorption kinetics constanta (k), the data is getting lower along with the increase in the initial concentration of Cu (II). This is because Cu(II) ion in solution are reactive to bacterial cells, which can cause cell damage result death bacteria. Based on the results measurements of Pseudomonas putida after the biosorption using FTIR it can be seen that the presence of Cu (II) is bound to the bacterial cell wall. This can be seen from the shift of absorption peak at wave number 420.45 cm-1 which indicates the presence of Cu-O groups.